2021
DOI: 10.1002/hep.31766
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient Radiofrequency Ablation Promotes Hepatocellular Carcinoma Metastasis Through N6‐Methyladenosine mRNA Methylation‐Dependent Mechanism

Abstract: BaCKgRoUND aND aIMS:The dynamic N6methyladenosine (m 6 A) mRNA modification is essential for acute stress response and cancer progression. Sublethal heat stress from insufficient radiofrequency ablation (IRFA) has been confirmed to promote HCC progression; however, whether m 6 A machinery is involved in IRFA-induced HCC recurrence remains open for study. appRoaCH aND ReSUltS: Using an IRFA HCC orthotopic mouse model, we detected a higher level of m 6 A reader YTH N6-methyladenosine RNA binding protein 1-3 (YTH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 44 publications
1
54
0
Order By: Relevance
“…The role of RNA m6A modi cation has been increasingly recognized in various biological activities, such as stem cell development, immune response, and malignant progression, through affecting gene expression (36-40). Unexceptionally, evidence accumulated con rms that m6A modi cation involves every stage of HCC, ranging from tumor initiation to tumor growth and, nally, to metastatic dissemination (41)(42)(43). Our works further con rmed the ndings of mounting studies concluding the reliable role of m6A genes in predicting survival outcomes of cancer patients (44)(45)(46)(47).…”
Section: Discussionsupporting
confidence: 75%
“…The role of RNA m6A modi cation has been increasingly recognized in various biological activities, such as stem cell development, immune response, and malignant progression, through affecting gene expression (36-40). Unexceptionally, evidence accumulated con rms that m6A modi cation involves every stage of HCC, ranging from tumor initiation to tumor growth and, nally, to metastatic dissemination (41)(42)(43). Our works further con rmed the ndings of mounting studies concluding the reliable role of m6A genes in predicting survival outcomes of cancer patients (44)(45)(46)(47).…”
Section: Discussionsupporting
confidence: 75%
“…Theoretically, genetic changes occur in the cancer cells around the ablation site when cells are subjected to thermal stimulation, and the cancer cells of incomplete ablation show more aggressive progression than untreated cells. The previous publications have proven that this experiment can imitate the biological properties similar to residual liver tumor observed clinically [22][23][24][25]. Following another 24-h culture, HepG2 xenografts were removed and immediately protected by RNAsafer Stabilizer Reagent (OMEGA, Guangzhou, China) for RNA-seq detection.…”
Section: Nude Mouse Xenograft Modelmentioning
confidence: 86%
“…m6A modification has been found that plays an important role in the occurrence and development of tumor. For example, sublethal heat treatment increases EGFR m6A modification near the 5′UTR region and promotes its binding to YTHDF1, thereby enhancing the translation of EGFR mRNA and promoting hepatocellular carcinoma progression (Su et al, 2021). METTL3 dependent m6A modification could regulate the differentiation of T follicle helper cells (Yao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%